Effect of environmental factors (wave exposure and depth) and anthropogenic pressure in the C sink capacity of Posidonia oceanica meadows. (20th March 2017) - Mazarrasa, Inés; Marbà, Núria; Garcia‐Orellana, Jordi; Masqué, Pere; Arias‐Ortiz, Ariane; Duarte, Carlos M.
Abstract: Seagrass are among the most important natural carbon sinks on Earth with Posidonia oceanica (Mediterranean Sea) considered as the most relevant species. Yet, the number of direct measurements of organic carbon burial rates in P. oceanica is still scarce and the effect of local environmental factors remains largely unexplored. In addition, P. oceanica meadows are declining due to the increase in anthropogenic pressure in coastal areas during the last century. The aim of this study is to assess the recent carbon sink capacity of P. oceanica and particularly the effect of human pressure and two environmental factors, water depth and exposure to wave energy (based on a fetch index), on the carbon burial rate since 1900. We conducted an extensive survey of sediment cores in meadows distributed across a gradient of depth, fetch, and human pressure around The Balearic Islands. Sediment and carbon accumulation rates were obtained from 210 Pb concentrations profiles. Top‐30 centimeters carbon stocks (6.1 ± 1.4 kg C m −2 ) and burial rates (26 ± 6 g C m −2 yr 1 ) varied up to fivefold across meadows. No significant effect of water depth in carbon burial rates was observed. Although fetch was significantly correlated with sediment mean grain size, confirming the effect of wave exposure in the patterns of sedimentation, fetch alone could not explain the differences in carbon burial rates among the meadows examined. Human pressure affected carbon burial rates, leading to increased rates since the onset of the rise in anthropogenic pressure, particularly so in sheltered meadows supporting high human pressure.